2003
DOI: 10.1007/bf02723810
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis in HIV

Abstract: A five and half-year-old boy with arthritis involving large joints is reported. The child was found to be seropositive for HIV. Various rheumatological manifestations have been described in adults with HIV infection. To the best of our knowledge, this is the first report of HIV infection presenting as arthritis in pediatric age group in Indian literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…HIV infection has a peculiar tendency for autoimmune and inflammatory phenomena in the setting of profound immunosuppression. Arthritis can occur at any stage of the disease [6]. In adults, acquired immunodeficiency syndrome related arthropathy has been classified into five groups namely (a) spondyloarthropathic arthritis (Reiter's syndrome, psoriatic arthritis and undifferentiated spondyloarthropathy), (b) HIV associated arthritis, (c) painful articular syndrome, (d) acute symmetric polyarthritis, (e) septic arthritis [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV infection has a peculiar tendency for autoimmune and inflammatory phenomena in the setting of profound immunosuppression. Arthritis can occur at any stage of the disease [6]. In adults, acquired immunodeficiency syndrome related arthropathy has been classified into five groups namely (a) spondyloarthropathic arthritis (Reiter's syndrome, psoriatic arthritis and undifferentiated spondyloarthropathy), (b) HIV associated arthritis, (c) painful articular syndrome, (d) acute symmetric polyarthritis, (e) septic arthritis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our patient had predominant involvement of knee joint leading to contractures, and involvement of other joints since past 2 months. Ahuja et al [6] reported a HIV infected child with multiple joint arthropathy, past history of tuberculosis, herpes zoster and prolonged fever. Similarly, our patient also had tuberculosis and herpes zoster in the past with wasting and multiple joint diseases suggesting that in a patient with polyarthropathy and infections an underlying immunodeficiency should be suspected in a high prevalence setting.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] The data on the occurrence of HIV arthropathy in the pediatric age group is sparse, the first case in India being reported in 2003. [ 2 ] The various causes of the HIV arthropathy include arthralgia, spondyloarthropathies (SpA), reactive arthritis (Reiter's syndrome), psoriatic arthritis, HIV-associated arthritis, and septic arthritis. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Methotrexate and immunosuppressive drugs may be useful but can trigger opportunistic infections and progression to frank AIDS. 5 We highlight the importance of keeping HIV infection in mind when dealing with children having unexplained largejoint arthritis. …”
mentioning
confidence: 98%